AutoCAD® 2D for Geometric Design of Terbanggi Besar–Pematang Panggang Highway (Sta.28+650 – Sta.53+650) - Gunawan, Ratih Yuliani; Rifai, Andri Irfan; Irianto, Muhamad Alamsyah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
With a length of approximately 2,818 kilometers, the Trans Sumatra Highway connects cities from Lampung to Aceh. Meticulous planning and adherence to the geometric and technical requirements of the route are required to provide good road service. The purpose of this paper is to specifically redesign the current route on the Terbanggi Besar-Pematang Panggang section of the highway. The information used in this report as a guide for re-planning came from the results of field surveys. The geometric design of this highway was carried out using the manual calculation method based on the Road Design Standards of Indonesia 2021 and visualized using AutoCAD® 2D. Based on available data, a design speed (VD) of 120 kph is determined according to the maximum value on flat terrain on the highway. As a result of data processing on a particular road section, a horizontal alignment with a full circle curve type with a radius of 1500 m was created. Meanwhile, a sag vertical curve type is obtained in the vertical alignment with a length value at one point of the curve (L) of 75.6 m